Studies on the nutrition of the Tea Tortrix, Homona Coffearia Nietner (Lepidoptera: Tortricidae) with particular emphasis on the requirements of Carbohydrates, Amino Acids, Fatty Acids and Sterols - Gnanapragasam, Nalini Chandramalar (Faculty of Science, University of Colombo, 1982)
The present investigation was undertaken to further improve the artificial diets developed earlier to rear the tea tortrix, Homona coffearia Nietner in vitro (M.Phil Thesis, Gnanapragasam, 1979) and perfect a completely defined one (holidic diet) to study in detail, the optimal requirements of various essential dietary ingredients (a) carbohydrates, (b) amino acids, (c) fatty acids and (d) sterols, needed for normal growth and development of this insect through successive generations.